Sur la convergence des quelques intégrales du type Laplace—Stiltjes - Strelits, Ch.; Miškelevičius, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. Стрелиц, А. Мишкелявичус. О сходимости некоторых интегралов типа Лапласа—СтилтьесаŠ. Strelicas, A. Miškelevičius. Kai kurių Laplaso—Stiltieso tipo integralų konvergavimo klausimu